FoxO3a nuclear localization and its association with beta-catenin and Smads in IFN-alfa-treated hepatocellular carcinoma cell lines - Ceballos Mancini, María Paula (2014)
Interferon-a2b (IFN-a2b) reduces proliferation and increases apoptosis in hepatocellular carcinoma cells by decreasing b-catenin/TCF4/Smads interaction. Forkhead box O-class 3a (FoxO3a) participates in proliferation and apoptosis and interacts with b-catenin and Smads. FoxO3a is inhibited by Akt, IkB kinase b (IKKb), and extracellular-signal-regulated kinase (Erk), which promote FoxO3a sequestration in the cytosol, and accumulates in the nucleus upon phosphorylation by c-Jun N-terminal kinase ( JNK) and p38 mitogen-activated kinase (p38 MAPK). We analyzed FoxO3a subcellular localization, the participating kinases, FoxO3a/b-catenin/ Smads association, and FoxO3a target gene expression in IFN-a2b-stimulated HepG2/C3A and Huh7 cells. Total FoxO3a and Akt-phosphorylated FoxO3a levels decreased in the cytosol, whereas total FoxO3a levels increased in the nucleus upon IFN-a2b stimulus. IFN-a2b reduced Akt, IKKb, and Erk activation, and increased JNK and p38 MAPK activation. p38 MAPK inhibition blocked IFN-a2b-induced FoxO3a nuclear localization. IFN-a2b enhanced FoxO3a association with b-catenin and Smad2/3/7. Two-step coimmunoprecipitation experiments suggest that these proteins coexist in the same complex. The expression of several FoxO3a target genes increased with IFN-a2b. FoxO3a knockdown prevented the induction of these genes, suggesting that FoxO3a acts as mediator of IFN-a2b action. Results suggest a b-catenin/Smads switch from TCF4 to FoxO3a. Such events would contribute to the IFN-a2b-mediated effects on cellular proliferation and apoptosis. These results demonstrate new